Moving Toward Inclusion: Participant Responses to the Inclusive SciComm Symposium - Smith, Hollie; Menezes, Sunshine; Canfield, Katherine; Guldin, Rachel; Morgoch, Meredith; McDuffie, Katharine (Frontiers in Communication, 2020)
This study shares key findings from evaluation research for Inclusive SciComm: A Symposium on Advancing Inclusive Public Engagement with Science. The symposium, organized by the University of Rhode Island’s Metcalf Institute for Marine & Environmental Reporting with support from partner organizations, took place on September 28-29, 2018 at the University of Rhode Island. Pre- and post-symposium surveys showed that after attending the symposium, participants reported higher levels of knowledge about and confidence in implementing inclusive approaches to science communication. Participants also exhibited three types of response orientations: emotion, knowledge, and action.